2022
DOI: 10.37190/ppmp/145667
|View full text |Cite
|
Sign up to set email alerts
|

Selective comminution and grinding mechanisms of spent carbon anode from aluminum electrolysis using ball and rod mills

Abstract: The recovery of spent carbon anode (SCA) materials plays important roles in environment protection and resources recycling, while this cannot be efficiently achieved without liberation. In this study, grinding characteristics of spent carbon anode from aluminum electrolysis in both ball mill and rod mill were analyzed, and compared based on the utilization of the selective Fuerstenau upgrading curves. In addition, the different grinding mechanisms of ball and rod milling were evaluated by analyzing the shape f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The operational speed of the ball mill was set at 115 rpm (62.16% of critical rotational speed). The calculation of critical rotational speed for ball mill refers to the published literature ( Ni et al, 2022 ). A mass of 200 g carbon anode slag with the size of −1 mm was fed into the ball mill.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The operational speed of the ball mill was set at 115 rpm (62.16% of critical rotational speed). The calculation of critical rotational speed for ball mill refers to the published literature ( Ni et al, 2022 ). A mass of 200 g carbon anode slag with the size of −1 mm was fed into the ball mill.…”
Section: Methodsmentioning
confidence: 99%
“…Comparing Figures 6A,B, it is found that there were significantly more black carbon particles in the product after grinding treatment than in the raw carbon anode slag, indicating that cryolite Frontiers in Chemistry frontiersin.org particels were enriched in the fine-grainded carbon particles were enriched in the coarse-grainded fraction. This was because there was a difference in hardness between cryolite and carbon particles, which led to the selective crushing of carbon anode slag in the grinding process (Ni et al, 2022).…”
Section: Grinding Timementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the difference in the crushing resistance of different mineral components is essentially a comprehensive manifestation of the difference in impact resistance and grinding resistance [22][23][24][25], and the macroscopic result is the selective crushing of minerals. Although relevant scientific researchers discovered the selective crushing phenomenon a long time ago and have since carried out corresponding theoretical research work [26][27][28], no one has yet studied the selective crushing phenomenon from the perspective of mineral impact crushing.…”
Section: Introductionmentioning
confidence: 99%